Bifunctional Tailoring of Platinum Surfaces with Earth Abundant Iron Oxide Nanowires for Boosted Formic Acid Electro-Oxidation - Bilquis Ali Al-Qodami; Heba H. Farrag; Sayed Youssef Sayed; Nageh K. Allam; Bahgat E. El-Anadouli; Ahmad M. Mohammad (Journal of Nanotechnology)
To expedite the marketing of direct formic acid fuel cells, a peerless inexpensive binary FeOx/Pt nanocatalyst was proposed for formic acid electro-oxidation (FAO). The roles of both catalytic ingredients (FeOx and Pt) were inspired by testing the catalytic performance of FAO at the FeOx/Au and FeOx/GC analogies. The deposition of FeOx proceeded electrochemically with a post‐activating step that identified the catalyst’s structure and performance. With a proper adaptation for the deposition and activation processes, the FeOx/Pt nanocatalyst succeeded to mitigate the typical CO poisoning that represents the principal element deteriorating the catalytic performance of the direct formic acid fuel cells. It also provided a higher (eightfold) catalytic efficiency than the bare Pt substrates toward FAO with a much better durability. Field-emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) were all employed to inspect, respectively, the surface morphology, bulk composition, and crystal structure of the catalyst. The electrochemical impedance spectra could correlate the charge transfer resistances for FAO over the inspected set of catalysts to explore the role of FeOx in mediating the reaction mechanism.